Maternal Risk Factors Associated with Low Birth Weight among in Term Newborns in Abadan University of Medical Sciences: A Nested Case-Control Study - Neda Amoori; Haydeh Ghajari; Belghis Afkaneh (Shiraz University of Medical Sciences, 2024)
Background: Low birth weight (LBW) can cause complications and disorders in the future life of newborns. This study aimed to investigate maternal risk factors affecting low birth weight among term newborns in the affiliated cities of Abadan University of Medical Sciences based on a nested case-control study.Methods: In this study, based on the nested case-control design, namely with the risk set sampling approach, the case and control groups were selected. All in-term newborns born since the beginning of 2018, with less than 2500g birth weight, were considered as the case group. Two were randomly selected as controls from newborns born in the same time frame and geographical location and with over 2500g birth weight. The selection ratio of the cases to control was 1:2. The questionnaires were completed from the beginning of 2019 to the end of 2020. To describe the data, descriptive statistical indicators including mean, standard deviation, frequency, and logistic regression were used in this method.Results: The results of this study indicate that the factors affecting LBW are maternal age, number of pregnancies, number of abortions, history of stillbirth, history of bleeding, mother's BMI, number of births, twins, and gestational intervals.Conclusion: It is suggested that health policymakers should pay special attention to the necessary interventions for mothers with special pregnancy care conditions. In addition, it is necessary to pay more attention to the continuation and improvement of the quality of educational programs for health and medical personnel to increase the mothers' awarenessregarding the maintenance of a healthy lifestyle during pregnancy.